Iatrogenic esophageal perforation with mediastinitis, multidisciplinary management: a case report - Mancera, Juliana; Ariza, Anibal M.; Pelaez, Mauricio; Benavides, Sebastian; Márquez, Alfonso C. (International Surgery Journal, 2021)
Acute mediastinitis is a low incidence pathology, but it is associated with a high mortality rate. Iatrogenic lesions are the most common cause of mediastinitis secondary to esophageal perforation. Early diagnosis and surgical treatment are the most important factors in the treatment of patients with this condition. 83-year-old female patient, with a history of left saphenectomy due to venous insufficiency with difficult intubation two days prior to the emergency consultation. She was admitted to the emergency room due to dyspnea, hemoptysis, chest pain, and right hemifacial edema. A chest tomography was performed with findings suggestive of esophageal perforation or airway injury. Later, in an upper digestive tract study, extravasation of the contrast medium was documented in the right posterolateral wall of the cervical esophagus with a collection in the middle mediastinum. The patient was taken for drainage of mediastinitis by right thoracoscopy and the presence of a perforation in the cervical esophagus was confirmed with an intraoperative endoscopy. Esophageal repair was performed, with drainage of the prevertebral space and the superior mediastinum by a left longitudinal cervicotomy. Postoperatively, she received antibiotic and enteral nutritional support by a nasojejunal tube. Low output fistula of the cervical esophagus, organized by a drain, was documented, which closed after 4 weeks of conservative management. Iatrogenic esophageal perforation with mediastinitis is a very rare entity with a high mortality. Early surgical treatment is the most important prognostic factor in patients with mediastinitis due to esophageal perforation.